Effect of Pharmacist Interventions on Medication Adherence to Capecitabine in Cancer Patients: A Systematic Review - Puspitasari, Atika Wahyu; Kristina, Susi Ari; Satibi; Prabandari, Yayi Suryo (Indonesian Journal of Pharmacy, 2022)
Oral chemotherapy poses challenges regarding patient medication adherence. Pharmacists play a vital role in supporting medication adherence to achieve the effectiveness of therapy. This review aimed to evaluate the impact of pharmacist interventions on medication adherence in patients with cancer taking capecitabine. The literature was systematically reviewed using Scopus, ScienceDirect, Sage Journal, Springer Link, PubMed, and Google Scholar. Key text words included “adherence, pharmacist intervention, capecitabine, oral chemotherapy, and cancer.” We collected original articles published from January 2010 to June 2021 in English that reported pharmacist interventions to enhance capecitabine adherence in adult patients with cancer and assessed adherence rates pre- and post-intervention. Two independent researchers extracted data relevant to inclusion criteria and determined the methodological quality of studies using the Joanna Briggs Institute Critical Appraisal Checklist Tools. A total of 4179 articles were retrieved, of which five were eligible for review. The most common pharmacist intervention strategy was a combination of patient education, with oral and written information provided. Components of patient education were the characteristics of capecitabine, including its mechanism of action, side effects, and their management; current therapeutic regimen; importance of adherence; and risk of non-adherence. Pharmacist interventions provide beneficial impacts on medication adherence, beliefs about medication, and tolerability of side effects. The findings suggest that pharmacist interventions support medication adherence improvement and highlight the role of pharmacist interventions in pharmaceutical oncology care services. Further studies are necessary to assess pharmacist interventions’ long-term effects and clinical outcomes.